2011
DOI: 10.1159/000324657
|View full text |Cite
|
Sign up to set email alerts
|

Tear Film Function in Patients with Seasonal Allergic Conjunctivitis Outside the Pollen Season

Abstract: Background: Seasonal allergic conjunctivitis can manifest itself through tear film instability and symptoms of eye discomfort during the pollen season. This study investigated whether seasonal allergic inflammation defines tear film instability outside the season. Methods: Twenty-three control subjects and 13 ragweed-allergic patients were involved (21 female, 15 male; mean age 26.6 ± 5.4 years). Outside the pollen season, subjective ocular symptoms, non-invasive tear film break-up time, lower tear meniscus he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…41,42 The difference is presumably due to the differential effects between PM2.5 and other allergens, as it was reported that seasonal allergic inflammation did not cause permanent tear film instability outside the pollen season. 43 Alternatively, the effects of an allergic induction in the acute phase are likely to differ from those long-term consequences. With long-term AC, tear film stability is usually impaired as a result of reduced conjunctival goblet cell density, often concurrent with decreased tear secretion, making it very difficult to perform differential diagnosis between AC and dry eye.…”
Section: Discussionmentioning
confidence: 99%
“…41,42 The difference is presumably due to the differential effects between PM2.5 and other allergens, as it was reported that seasonal allergic inflammation did not cause permanent tear film instability outside the pollen season. 43 Alternatively, the effects of an allergic induction in the acute phase are likely to differ from those long-term consequences. With long-term AC, tear film stability is usually impaired as a result of reduced conjunctival goblet cell density, often concurrent with decreased tear secretion, making it very difficult to perform differential diagnosis between AC and dry eye.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a few researches on tear film stability in intermittent forms of OA reported that VKC patients seem to show a shortened BUT even in the quiet phases of the disease, [11] while SAC patients don't have decreased tear film stability outside the pollen season. [17] In the Vicious Circle of DED, tear film instability may be due to different mechanisms, including Meibomian glands (MGs) and lipid layer changes on the one hand and mucins alterations on the other. [18**, 19*] A few imaging studies assessed MGs in different forms of OA, [20*] including AKC, VKC and PAC.…”
Section: Oa and Tear Film Instabilitymentioning
confidence: 99%
“…A study in humans has shown that seasonal allergic conjunctivitis may result in reversible tear film instability (11). However, no histological examination was performed to confirm the clinical results.…”
Section: Discussionmentioning
confidence: 99%